The Role of Coffee Trade in Shaping Ethiopia’s Economic Development from the 1960s to Present - Alem Tadesse Girmay (Law and Economy, 2024)
This study examines the role of coffee trade in shaping Ethiopia’s economic development from the 1960s to the present. It explores the evolution of Ethiopia’s coffee industry through key policy transformations, market liberalization, and economic reforms, highlighting their impact on national export revenues, foreign exchange reserves, employment creation, and rural economic development. The analysis addresses the challenges faced by Ethiopia’s coffee sector, including climate change, market volatility, and global competition, while also identifying opportunities for growth through sustainability practices, certification, and market diversification. Finally, the study outlines strategic pathways for future development, focusing on enhancing productivity, building resilient supply chains, and aligning coffee trade strategies with broader national development goals.